Question
upstudy study bank question image url

(d) Determine (by showing all the steps) the equilibrium point(s) of the below differential equation, by strictly using an analytical approach (4 marks penalty if inspection is used). \[ \frac{d y}{d t}=-65-2\left(\sqrt{y^{3}-1}\right)^{-1}+3\left(\sqrt{y^{3}-1}\right)^{-1} \]

Ask by Jimenez Pope. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The equilibrium point is \( y = \sqrt[3]{\frac{4226}{4225}} \).

Solution

To determine the equilibrium point(s) of the differential equation \[ \frac{dy}{dt} = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1}, \] we need to find the value(s) of \( y \) where \( \frac{dy}{dt} = 0 \). ### Step 1: Set the Differential Equation to Zero Set \( \frac{dy}{dt} = 0 \): \[ 0 = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1} \] ### Step 2: Simplify the Equation Combine the terms involving \( \left(\sqrt{y^{3}-1}\right)^{-1} \): \[ 0 = -65 + \left(-2 + 3\right)\left(\sqrt{y^{3}-1}\right)^{-1} \] \[ 0 = -65 + \left(1\right)\left(\sqrt{y^{3}-1}\right)^{-1} \] \[ 65 = \left(\sqrt{y^{3}-1}\right)^{-1} \] ### Step 3: Solve for \( \sqrt{y^{3}-1} \) Take the reciprocal of both sides: \[ \sqrt{y^{3}-1} = \frac{1}{65} \] ### Step 4: Square Both Sides Square both sides to eliminate the square root: \[ y^{3} - 1 = \left(\frac{1}{65}\right)^{2} \] \[ y^{3} - 1 = \frac{1}{4225} \] ### Step 5: Solve for \( y^{3} \) \[ y^{3} = 1 + \frac{1}{4225} \] \[ y^{3} = \frac{4225}{4225} + \frac{1}{4225} = \frac{4226}{4225} \] ### Step 6: Take the Cube Root \[ y = \sqrt[3]{\frac{4226}{4225}} \] ### Conclusion The equilibrium point is: \[ y = \sqrt[3]{\frac{4226}{4225}} \] **Final Answer:** After simplifying, the sole equilibrium is the real root of y³ = 4226⁄4225. Thus, y = ∛(4226 ⁄ 4225)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To find the equilibrium point(s) of the given differential equation \[ \frac{d y}{d t} = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1}, \] we start by setting the right-hand side equal to zero: \[ 0 = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1}. \] This simplifies to: \[ 0 = -65 + \left(\sqrt{y^{3}-1}\right)^{-1}. \] Rearranging gives us: \[ \left(\sqrt{y^{3}-1}\right)^{-1} = 65. \] Taking the reciprocal, we obtain: \[ \sqrt{y^{3}-1} = \frac{1}{65}. \] Next, we square both sides: \[ y^{3} - 1 = \left(\frac{1}{65}\right)^{2}. \] Calculating \(\left(\frac{1}{65}\right)^{2}\): \[ y^{3} - 1 = \frac{1}{4225}. \] Adding 1 to both sides provides: \[ y^{3} = 1 + \frac{1}{4225} = \frac{4225 + 1}{4225} = \frac{4226}{4225}. \] Taking the cube root of both sides gives us the equilibrium point: \[ y = \sqrt[3]{\frac{4226}{4225}}. \] This is the analytical process to find the equilibrium point(s).

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy